Question #eb426

1 Answer
Apr 12, 2017

Answer:

See the entire solution process below:

Explanation:

First, use this rule of exponents to rewrite this expression:

#x^color(red)(a) = 1/x^color(red)(-a)#

#(6y)^color(red)(-4) = 1/(6y)^color(red)(- -4) = 1/(6y)^4#

If we want to further simplify the expression we can use these rules of exponents:

#a = a^color(red)(1)# and #(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#

#1/(6y)^4 = 1/(6^color(red)(1)y^color(red)(1))^color(blue)(4) = 1/(6^(color(red)(1) xx color(blue)(4))x^(color(red)(1) xx color(blue)(4))) = 1/(6^4y^4) = 1/(1296y^4)#